Case Report: Should Regorafenib be prescribed as a continuous schedule in gastrointestinal stromal tumors? Three case reports on Regorafenib personalized schedule - Grimaudo, Maria Susanna; Laffi, Alice; Gennaro, Nicolò; Fazio, Roberta; D’Orazio, Federico; Samà, Laura; Siracusano, Licia Vanessa; Sicoli, Federico; Renne, Salvatore Lorenzo; Santoro, Armando; Bertuzzi, Alexia Francesca (Frontiers in Oncology, 2023)
Introduction Regorafenib is a tyrosine kinase inhibitor (TKI) approved in metastatic gastrointestinal stromal tumor (GIST), colorectal cancer, and hepatocarcinoma. Anyway, the toxicity profile of Regorafenib standard schedule is associated with poor compliance and a high rate of discontinuation. For this reason, there is a growing need for a Regorafenib personalized schedule emerging from the scientific community. Objective The aim of this case series was to describe the experience of our sarcoma referral center with the continuous administration of Regorafenib as an alternative regimen to treat metastatic GIST patients. Methods We retrospectively collected clinical, pathological, and radiological data of patients with metastatic GIST treated with daily personalized Regorafenib at a single tertiary referral center from May 2021 to December 2022. Results We identified three patients fulfilling the inclusion criteria. The average follow-up since the start of Regorafenib was 19.1 months (12–25 months). All three patients had started a standard third-line Regorafenib schedule according to guidelines. The reasons for switching to a continuous schedule were as follows: exacerbation of symptoms during week-off treatment in the first patient, a serious adverse event (AE) in the second patient, and a combination of both conditions in the third. After switching, none of the patients reported severe AEs, and they improved control of tumor-related symptoms. Two of the patients experienced disease progression after 16 months (9 months of which is continuous schedule) and 12 months (8.1 months of which is continuous schedule) of Regorafenib, respectively; the third patient is still receiving continuous Regorafenib at the time of writing, with a progression-free survival of 25 months (14 months after the modified schedule start). Conclusion With a similar efficacy and lower toxicities, a daily, personalized Regorafenib schedule seems to be a promising alternative to the standard regimen for metastatic GIST patients, including the frail ones. Further prospective analyses are needed to confirm the safety and efficacy of such regimen.